O uso de metaheurísticas aplicadas ao problema de alocação de espectro e rota em redes ópticas elásticas - Gusmão , Renê Pereira de (2014)
In this work the problem of routing and route allocation (RSA) for elastic optical networks has been studied. This is similar to the problem of routing and wavelength allocation problem, the latter being characteristic routed optical networks in wavelengths. The problem RSA aims to allocate the least amount of resources to elastic optical network so it can cater to the maximum number of demands set out in customer traffic matrix. Besides the study of the problem, in this paper, two metaheuristics were implemented, which were the Iterated Local Search (ILS) and the Greedy Randomized Adaptive Search Procedure (GRASP), which use SSA and LP-CA mathematical models in the local search phase. To implement metaheuristics and mathematical models, we used IBM ILOG CPLEX IDE. The results are presented in graphs, which showed that metaheuristics able to be efficient and competitive, with good quality solutions in an acceptable and even lower than the results presented by accurate modeling computational time. Finally, this paper presents a discussion of the advantages and limitations of this study, and presents directions for future work in this field of study.